Variation in photo- and thermal- sensitivities among local, improved and exotic kenaf accessions in Nigeria (2007)
The response of two local, eleven improved and one exotic accessions of kenaf to daylength was determined by their increase in vegetative growth after flowering in 2004. Seven out of the fourteen accessions were planted every 4 months in 2005 to determine their sensitivity to natural variations in daylength, temperature, solar radiation and relative humidity in tenns of days to flower initiation, percentage gain in height after flowering and fibre yield. The plants took longer days to flower at longer daylength and higher temperature. Differences among accessions were significant for all traits in 2004. Days to flowering were more in December than in April and August, the number of days differing among accessions. Percentage gain in height after flowering differed with planting date only in the heat-tolerant accessions and was highest in December. Differences in fibre yield were not significant among accessions when planted in August, but differed significantly in April and December. On the average, fibre yield was highest in December and lowest in August. A grouping of the accessions based on their responses to daylength for both years of study was consistent. The implications of these findings in development of agronomically superior varieties and production of raw materials all round the year in Nigeria are discussed.